Selection In Segregating Population Of Tomato (Solanum Lycopersicum) For Growth, Yield And Virus Resistance (Bangladesh Journal of Agricultural Research, 2011)
Nineteen segregating lines of tomato were evaluated at the Horticulture Research Centre of BARI during winter season of 2008-2009 with a view to developing high yielding virus resistant varieties. Wide variation was observed among the lines in respect of number of fruits per plant (13.5-38.3), individual fruit weight (56.8-162.3g), fruit yield per plant (1.28-2.40 kg), and locule number of fruit (2.0-8.5). The highest number of fruits per plant was observed in the line 14-1-1-1-1, but its corresponding individual fruit weight was only 58.4g. The line 15-3-4-2-1 had the highest individual fruit weight (162.3g). The highest fruit yield was recorded from the line 15-3-4-2-1 (81.6 t/ha), which was closely followed by the line 15-1-2-2-1 (79.5 t/ha). Thirteen genotypes were found free from virus infection up to 60 days after transplanting, while the rest had very low (1.4 - 2.8%) virus incidence. Among the entries, considering yield and virus reaction, the lines, 8-1-3-4-1, 8-1-3-1-1, 8-1-3-2-2, 14-1-1-1-1, 15-3-4-2-1, 15- 1-2-2-1 and 15-1- 2-1-2 were selected for further evaluation and recommendation as varieties.  Keywords: Segregating population; tomato. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9278 BJAR 2011; 36(3): 507-512